Faktor-Faktor yang Mempengaruhi Implementasi Kebijakan Pengelolaan Sampah di Kota Pekanbaru (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimd to measure the factors influencing the implementation of waste management policy in Pekanbaru City based on Edward III’s theory, as well as to identify other factors beyond the fours dimensions of Edward III taht affect policy implementation. The research employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected from 100 respondent consisting of officials of the Environmental and Sanitation Agency (DLHK), the community, and the stakeholders realted to Regionel Regulation No. 8 of 2014 Pekanbaru City. Qualitative data were obtained through in-depth interviews with six key informants to strengthen the quantitave findings. Regression analysis indicates that communication contributes 9,4%, resources 12,6%, disposition 12,5%, and bureaucratic structure 30,2% to the implementation of waste management policy in Pekanbaru. Simultaneously, the four factors have a positive and significant influence with a total cuontribution of 64,7% while the remaining 35,3% is explained by other factors. The interview results further reveal that synergy among factors and the substance of the policy itself also play a role in influencing the implementation of waste management policy. Keywords: Communication, resources, disposition, bureaucratic structure, policy implementation, waste managament in Pekanbaru